The development of the magnetic system of sensor for PMR-analyser - A. Y. Svinin; R. S. Каshaev; O. V. Коzelkov (Известия высших учебных заведений: Проблемы энергетики)
The enhancement of the measuring instruments accuracy has always been the most crucial task for engineers and scientists. In particular, in the field of nuclear magnetic resonance, the creation of uniform magnetic field often defines the results of measurements, therefore the main task of this study is to develop Halbach magnet array based on design characteristics of developing NMR-analyzer. The research describes the development process of the main sensor’s magnetic system components for continuous-flow portable NMR-analyzer. The scientific paper makes a different variations analysis of Halbach magnet arrays on the degree of the magnetic field homogeneity, shows the process of development and production of the 3D-framework for Halbach magnet array for NMR-analyzer. The article also gives information on the design of quartz generator based on Pierce oscillator circuit for receiver-transmitter coil of the NMR-analyzer’s sensor. The results could be useful for the magnetic sensors design with high degree of homogeneity, measuring instruments and devices using the method of nuclear magnetic resonance in its foundation.